Tracker and Monitoring System for Self-Quarantined Individuals - Mazuki, Hazwan; Ismail, Shahrinaz (Journal of Computing Technologies and Creative Content, 2021)
Quarantine has been establish as a method to reduce the spread of infectious disease. Ensuring maximum compliance of quarantined individual has been the key to a successful quarantine. Tracking the movement and monitoring of vitals such as temperature can help health officials in their war against infectious diseases such as Coronavirus Disease 2019. The tracker and monitoring of quarantined individual system is developed with this goal in mind. The combination of device and system that carefully tracks and monitors quarantined individuals can be used to alleviate the task of health officials and reduce the risk of an outbreak from developing further.